Factors Related To Work Stress On Employees Of PT Angkasa Pura I Makassar During The Covid-19 Pandemic - Lalu Muhammad Saleh; Zulfani Asma Fitri; A. Muflihah Darwis (Lambung Mangkurat University, 2022)
People’s life during the COVID-19 pandemic experienced multiple stressors because they worried would be infected by COVID-19, worried about dying and losing family members and friends as well as stressed due to layoffs, and also experienced an income decrease. One of the companies in Indonesia that have been affected by the COVID-19 pandemic is PT Angkasa Pura Airports. The objective of this study is to determine the factors related to work stress on employees of PT Angkasa Pura I Makassar during the COVID-19 pandemic. This research uses an analytic observational study with a cross-sectional study. The population in this research is employees who work at PT Angkasa Pura I Makassar totaling 229 people with a total sample of 146 people. The sample was collected by proportional random sampling. Data were analyzed using Stata in univariate and bivariate by chisquare test. The results showed that respondents experienced mild stress (10.3%), moderate stress (66.4%), and severe stress (23.3%). Statistical test results showed that age (p=0.000), workload (p=0.001), physical environment (p=0.043), social support (p=0.034) had a relationship with work stress while gender (p=0.220), and the role conflict variable (p= 537) has no relationship with work stress. There is a relationship between age, workload, physical environment, and social support with work stress and there is no relationship between gender and role conflict with work stress.